Literary prose Reasons and reasons of formation fields - قهرمان شیری (مطالعات زبانی و بلاغی)
Whereas the onset of literary prose is related to ââ13âth âcentury A.D, but a large part of its history is returned to âexisting field in former centuries. Iranian association with âArabic and Islamic languages and culture through schools, âstudies, daily deeds and rites and also translating Arabic texts âto Persian has a basic influence on both changing Khorasaniâs âstyle to Iraqiâs in prose and on formation procedures of âliterary prose from simple unadorned prose gradually at the âsame earliest days of Islam arrival to Iran. Instructing current âsciences of era, working in ministerial jobs especially âsecretary ship in courtiers and writing letters, centrality of âliteral meeting on diversionary and poem craftsmanship are âalso as the influential factors on literary prose, which are also âaccompanied the occupational obligations with literary prose âin addition to writers specialization and addresseeâ âexpectations. You can not also ignore passage of time on âinterest changing, self-censoring, political remarks, different âindividual experiences and extension increment of worldview âand dominancy on culture.â